Measuring the light meson nuclear modification factor in p-Pb collisions over an unprecedented $p_{\text{T}}$ range with ALICE - Joshua König (SciPost Physics Proceedings, 2022)
Differential invariant cross sections of light neutral mesons in p-Pb collisions at $\sqrt{s_{\text{NN}}}$ = 8.16 TeV and in pp collisions at $\sqrt{s}$ = 8 TeV have been measured up to very high transverse momentum ($p_{\text{T}}$). By combining independent reconstruction techniques available in ALICE using the EMCal and PHOS calorimeters as well as the central barrel tracking detectors, the combined spectra cover almost two orders of magnitude in $p_{\rm T}$ for the $π^{0}$ meson. The nuclear modification factor $R_{\text{pPb}}$ has been measured for the $π^{0}$ and $η$ mesons and is found to be consistent with NLO pQCD, CGC and energy loss calculations. Comparisons to the $R_{\text{pPb}}$ of $π^{0}$ measured in $\sqrt{s_{\text{NN}}}$ = 5.02 TeV hint at a stronger suppression at low $p_{\rm T}$ with increasing collision energy.